1984
DOI: 10.1002/zoo.1430030303
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of radiolabeled estradiol in the cat (Felis catus, L): A preliminary report

Abstract: The time course and end products of estradiol metabolism were studied in the domestic cat, which has been chosen as a model for steroid metabolism studies in nondomestic felidae. Radiolabeled estradiol was injected intravenously into three adult female cats; one had a spontaneous estrus, one was induced with folliclestimulating hormone, and one had been ovariohysterectomizeded; feces, urine, and blood were collected daily, and the radioactivity content was determined. Feces and urine contained 47 and 1% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
3

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 8 publications
0
10
1
3
Order By: Relevance
“…Although E 2 was not run as a radiolabeled standard in our HPLC analysis, HPLC results from several felids, the taxonomic group closest to the hyenids (Bininda-Emonds et al, 1999) from which we have HPLC data from feces, reveal that elution of E 2 often overlaps with that of E 1 (Brown et al, 1994), the largest immunoreactive peak in fecal samples from both pregnant and non-pregnant hyenas seen here. Additionally, radiolabeled estrogens in the domestic cat are predominantly excreted as unconjugated E 2 and E 1 (Brown et al, 1994;Shille et al, 1984), and we presume because of their close taxonomic relationship to hyenas, these particular estrogens may also be important immunoreactive metabolites in hyena feces. All of these factors suggest that an E 2 -specific antibody represents an acceptable choice for measuring estrogen in hyena feces.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although E 2 was not run as a radiolabeled standard in our HPLC analysis, HPLC results from several felids, the taxonomic group closest to the hyenids (Bininda-Emonds et al, 1999) from which we have HPLC data from feces, reveal that elution of E 2 often overlaps with that of E 1 (Brown et al, 1994), the largest immunoreactive peak in fecal samples from both pregnant and non-pregnant hyenas seen here. Additionally, radiolabeled estrogens in the domestic cat are predominantly excreted as unconjugated E 2 and E 1 (Brown et al, 1994;Shille et al, 1984), and we presume because of their close taxonomic relationship to hyenas, these particular estrogens may also be important immunoreactive metabolites in hyena feces. All of these factors suggest that an E 2 -specific antibody represents an acceptable choice for measuring estrogen in hyena feces.…”
Section: Discussionmentioning
confidence: 93%
“…Fecal steroid analysis, in particular, offers an attractive alternative to blood sampling in both wild and captive animals. For collecting samples frequently, non-invasively, and without disrupting normal behavior of individuals or groups, techniques have been developed to assay fecal estrogen concentrations in a number of other mammalian carnivores (Brown et al, 1994;Monfort et al, 1997;Onuma et al, 2002;Shille et al, 1984;Young et al, 2001). A preliminary study in captive Crocuta detected measurable amounts of radiolabeled estrogen in fecal matter, and indicated that feces, rather than urine, should prove useful for sampling of excreted steroid hormones (Koretz, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…O aumento das concentrações séricas de estrógeno, produzido pelos folículos ovarianos durante as fases de proestro e estro, causam proliferação das camadas de células do epitélio vaginal (Shille et al, 1984). Pequenas células saudáveis, próximas ao suporte sanguíneo, tornam-se maiores e mais irregulares à medida que se afastam da lâmina basal em direção ao lúmen e o núcleo diminui progressivamente, até se desintegrar (Herron, 1977).…”
Section: Discussionunclassified
“…Alguns autores descreveram ser comum a presença de leucócitos, principalmente durante as fases de metaestro e anestro da gata (Toniollo et al, 1995), embora outros tenham afirmado ser raro tal fato (Shille et al, 1984). A ocorrência de hemácias não é normal em nenhuma das fases do ciclo (Herron, 1977;Toniollo et al, 1995).…”
Section: Discussionunclassified
“…Portanto, o primeiro passo crucial para aplicação desta tecnologia é determinar a razão dos metabólitos de esteróides entre urina e fezes. O estudo do metabolismo do estradiol em gatos domésticos (Felis catus) demonstrou que mais de 95% deste esteróide é excretado nas fezes (SHILLE et al, 1990(SHILLE et al, , 1984. Além do mais, muitos estudos têm sugerido que os metabólitos de estradiol e/ou a progesterona são quantificáveis em fezes de felídeos não-domésticos, guepardo, Acinonyx jubatus (CZEKALA et al, 1994GROSS, 1992); tigre, Panthera tigris ; leão, P. leo ; caracal, F.…”
Section: Estrogêniosunclassified